The Effectiveness of Health Education Through Booklet and PowerPoint Media on Adolescents' Knowledge of the Impacts of Free Sex - Salsa Fadhila Zahra; Susilo Budi Pratama; Hema Dewi Anggraeni; Nina Anggraeni Noviasari (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Unprotected sex among adolescents remains a public health problem because it increases the risk of unintended consequences (KTD), sexually transmitted infections, and various psychosocial impacts. The low level of adolescent knowledge regarding the impact of unprotected sex is one of the factors that drives the need for health education. Appropriate educational media is expected to be able to increase adolescent knowledge more optimally. Method: This study used a quantitative method with a pretest-posttest control group design. Three of the four eleventh grade classes were assigned to the booklet intervention group, PPT, and the control group. Data analysis used the Wilcoxon, Kruskal-Wallis, and post-hoc Mann-Whitney tests with a significance level of 5%. Results: Adolescent knowledge increased significantly in the booklet group (Z = -4.884; p = 0.000) and the PPT group (Z = -2.927; p = 0.003), while the control group did not show any significant changes (Z = -1.764; p = 0.078). The Kruskal-Wallis test showed a significant difference in knowledge increase between the three groups (H = 41.078; p = 0.000), with a mean rank of 73.82 for the booklet group, 44.14 for the PPT group, and 29.95 for the control group. Conclusion: Health education through booklets and PowerPoint media is effective in increasing adolescents' knowledge about the impact of casual sex. Booklets are proven to be more effective than PowerPoint media, so they are recommended as reproductive health education media for adolescents.